Developing Interactive Multimedia for Informatics Learning to Support Quality Education (SDG 4) - Vera Irma Delianti; Winda Agustiarmi; Ganefri; Asmar Yulastri; Elfizon (Jurnal Penelitian Pendidikan IPA, 2026)
The rapid development of digital technology requires learning approaches that integrate interactive media to enhance student engagement and conceptual understanding. However, Informatics learning in many senior high schools is still dominated by teacher-centered instruction, which limits students’ opportunities to explore concepts actively. Therefore, innovative digital learning media are needed to support more interactive and student-centered learning environments. This study aims to develop and evaluate interactive multimedia for learning basic computer operations and software functions in Grade 10 Informatics. The research employed a Research and Development (R&D) approach using the Instructional Development Institute (IDI) model, which applies a systematic instructional design through three stages: define, develop, and evaluate. The study involved 30 tenth-grade students and two Informatics teachers at SMA Negeri 2 Bukittinggi, Indonesia. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning outcome tests using a one-group pretest–posttest design. The results show that the multimedia achieved very high validity (4.62) and excellent practicality (90.6%). The effectiveness test produced an N-gain score of 0.60, indicating a moderate level of effectiveness. These findings suggest that the multimedia is valid, practical, and moderately effective for supporting digital learning aligned with Sustainable Development Goal 4 (Quality Education).